2023
DOI: 10.1001/jamainternmed.2023.0750
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Post−COVID-19 Condition

Abstract: ImportancePost−COVID-19 condition (PCC) is a complex heterogeneous disorder that has affected the lives of millions of people globally. Identification of potential risk factors to better understand who is at risk of developing PCC is important because it would allow for early and appropriate clinical support.ObjectiveTo evaluate the demographic characteristics and comorbidities that have been found to be associated with an increased risk of developing PCC.Data sourcesMedline and Embase databases were systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
224
6
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 418 publications
(272 citation statements)
references
References 88 publications
33
224
6
9
Order By: Relevance
“…Therefore, the results of Dr Tsampasian and colleagues’ study regarding an association of COVID-19 vaccines with a reduced risk of developing PCC are inconsistent with the findings of other studies . Moreover, the researchers included only 4 studies to evaluate this risk and failed to adjust for combined vaccination before and after SARS-CoV-2 infection or after PCC diagnosis, potentially increasing the risk of bias and decreasing the certainty of the evidence. Importantly, the other studies enumerated previously also met the inclusion criteria but were excluded from the analysis.…”
contrasting
confidence: 94%
“…Therefore, the results of Dr Tsampasian and colleagues’ study regarding an association of COVID-19 vaccines with a reduced risk of developing PCC are inconsistent with the findings of other studies . Moreover, the researchers included only 4 studies to evaluate this risk and failed to adjust for combined vaccination before and after SARS-CoV-2 infection or after PCC diagnosis, potentially increasing the risk of bias and decreasing the certainty of the evidence. Importantly, the other studies enumerated previously also met the inclusion criteria but were excluded from the analysis.…”
contrasting
confidence: 94%
“…In Reply We thank Dr Yang and colleagues for their interest in our study and for highlighting that post−COVID-19 condition (PCC) is of important public health interest. They mention specific studies and rightly ask why these were not included in our meta-analysis.…”
supporting
confidence: 93%
“…We also found that female sex was associated with greater than five times increased odds of persistent cognitive ability disturbance and greater than seven times increased odds of persistent cognitive function disturbance. Other studies have also found females to be significantly more likely to report persistent neurocognitive symptoms following SARS‐CoV2 infection 21,31–35 . One study suggests that discrepancies in sex hormones related to inflammatory processes may also contribute to this difference we see in COVID‐19 response 36 .…”
Section: Discussionmentioning
confidence: 81%